1990
DOI: 10.1021/bk-1990-0447.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared Spectroscopy in Colloid and Interface Science

Abstract: This chapter reviews the wide range of colloidal systems amenable to investigation by FT -IR spectroscopy. Molecular level information about the interactions of amphiphilic substances in aggregates such as micelles, bilayers, and gels can be obtained and related to the appearance and stability of the various phases exhibited. The interactions of polymers, surfactants and proteins with interfaces, which substantially modify the solid -liquid or liquid -air interface in many important industrial and natural proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 13 publications
(14 reference statements)
1
35
0
Order By: Relevance
“…Further, the above peaks had undergone narrowing with time. These red shifting and narrowing of peaks indicate a dense and solid packing of octyl groups due to rearrangement of the attached molecules [7,[40][41][42][43]. Increasing peak areas of asymmetric peaks are observed with increase in silanization time.…”
Section: Ftir Spectroscopymentioning
confidence: 92%
“…Further, the above peaks had undergone narrowing with time. These red shifting and narrowing of peaks indicate a dense and solid packing of octyl groups due to rearrangement of the attached molecules [7,[40][41][42][43]. Increasing peak areas of asymmetric peaks are observed with increase in silanization time.…”
Section: Ftir Spectroscopymentioning
confidence: 92%
“…Numerous studies have employed FTIR to assess the conformation of organic molecules at interfaces. Changes to the conformation of these molecules as well as intermolecular interactions between them result in changes to the positions, widths, and heights of the asymmetric and symmetric bands t(C-H) bands (e.g., Scheuing, 1990;Vaia et al, 1994). For example, Zhu et al (2005) found that when alkylammonium molecules are sorbed to smectite, the t(CH 2 ) bands occur at low frequencies relative to the position of these bands in solid-state reference samples.…”
Section: Absorption In Monolayer Fashionmentioning
confidence: 99%
“…Unfortunately, the absorptions of C 0 2 itself obscure these modes. However, it has been suggested (Scheuing, 1990) that shifts in the position of the bending mode…”
Section: Ftir Spectroscopymentioning
confidence: 99%